Evaluation of Nutritional Interventions in Overcoming Chronic Energy Deficiency in Pregnant Women: A Case Study - Feprina, Yuni; J. Hadi, Anto; Ahmad, Haslinah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Chronic Energy Deficiency in pregnant women is one of the public health problems that can hurt the health of the mother and fetus. This study aims to evaluate the effectiveness of nutritional interventions in overcoming Chronic Energy Deficiency in pregnant women through a case study in one of the health centers in the Padangsidimpuan City area. Methods: A qualitative study with a case study design involving pregnant women with nutritional status with Chronic Energy Deficiency who received nutritional interventions over three months. This data was collected at the Padangmatinggi Health Center through in-depth interviews involving four primary informants and seven triangulation informants, which included document analysis and data analysis. Results: This study proves that the input aspects, namely sources of funds, infrastructure, forms of services, and supplementary feeding materials, are by the instructions, while the goals and human resources are not by the Supplementary Feeding Guidelines. It is appropriate for the planning, implementation, and recording process, but there are obstacles due to the uncertain dropping from the center. The increase in the size of the upper arm circumference is an output of the supplementary feeding program for pregnant women, but in reality, the cases of Chronic Energy Deficiency are still high. Conclusion: It can be concluded that the administration of supplementary feeding can only be monitored until distribution to pregnant women with Chronic Energy Deficiency, but consumption monitoring has not been carried out. This study suggests the importance of nutrition intervention programs integrated with health services at the health center level to reduce the prevalence of chronic energy deficiency in pregnant women and encourage healthier diets.